Cross-sectional study of HPV-16 infection in a population-based subsample of Hispanic adults. Issue 2 (4th February 2014) - Ortiz, A P; Unger, E R; Muñoz, C; Panicker, G; Tortolero-Luna, G; Soto-Salgado, M; Otero, Y; Suárez, E; Pérez, C M
Abstract : Objective: This study aimed to estimate the prevalence and correlates of seropositivity to human papillomavirus (HPV)-16 in a subsample of adults who participated in the parent study Epidemiology of Hepatitis C in the adult population of Puerto Rico (PR). Setting: The parent study was a population-based household survey aimed to estimate the seroprevalence of hepatitis C and other viral infections (hepatitis A, hepatitis B, HIV, and herpes simplex type 2) in PR (n=1654) between 2005 and 2008. Participants: A subsample of the last 450 consecutive adults aged 21–64 years, recruited between February 2007 and January 2008, who participated in the parent study and agreed to participate in HPV testing. Primary and secondary outcome measures: The samples were tested by ELISA for HPV-16 viral-like particle-specific immunoglobulin G. Information on sociodemographic, health, and lifestyle characteristics was collected. Logistic regression modelling was used to estimate the prevalence odds ratio (POR) to assess factors associated to HPV-16 seropositivity. Results: Prevalence of seropositivity to HPV-16 was 11.3%. Seroprevalence was higher in women (15.8%) than men (5.6%; p=0.001). After adjusting for age and sex, ever smokers (POR 2.06, 95% CI 1.08 to 3.92) and participants with at least five lifetime sexual partners (POR 2.91, 95% CI 1.24 to 6.81) were more likely to be HPV-16 seropositive. Conclusions: HPV-16 seropositivity is similar to that reported in the USA (10.4%) for NHANES 2003–2004 participants, although different assays were used in these studies. While future studies should evaluate HPV seroprevalence using a larger population-based sample, our results highlight the need to further understand the burden of HPV infection and HPV-related malignancies in PR, population with a low vaccine uptake.